The effect of perceptual understanding of physical and mental exercise in learning motor skills - Experimental research on a sample of Al Shoula Sports Club players, ages (18-20) years- (Journal of the College of Basic Education, 2023)
The first chapter: the definition of research1-1 Introduction and the importance of research:The rapid development in the field of physical education and sports and its various means has opened new horizons.new opportunities for researchers and students to acquire and develop information, abilities and motor skills..Motor learning is one of the most important major fields in the sciences of physical education and sports.It is the basis of the mathematical structure, and without it, the player would not be able to perform skills in such a complex manner.Compatibility when he was able to practice the most complex types of skill performance. Motor learning representsThe basis in the process of acquiring the means to help absorb the needs and motives to achieveset goals.Hence, the trainers and teachers are required to be familiar with the latest methods and methods.that enables them to use multiple strategies in training, and one of the most important types of training isMixing physical, mental and intellectual exercises, where mental exercise is one of the phenomenaIn the field of learning motor skills, it is the perception of the performance of the achievement without being associated with an apparent act.which causes significant positive transfer production in real skill learning and increases the level of arousal.the player and prepares him psychologically for the actual achievement if he is likely with physical exercise to reach the level ofThe conscious understanding of movement.Hence the importance of the research if the researchers intended to carry out this study in order to reach the importance ofPerceptual understanding between physical and mental exercise in learning motor skills.